Investigation of rotating detonation gas turbine cycle under design and off-design conditions. (1st February 2023) - Qi, Lei; Dong, Jingnan; Hong, Wenpeng; Wang, Mingtian; Lu, Tao
Abstract: As cycle efficiency of gas turbine can be significantly improved due to the pressure gain characteristic of rotating detonation combustion, a cycle calculation model of rotating detonation gas turbine based on component characteristic curves of a single shaft gas turbine of 25 MW and limited maximum flow capacity of rotating detonation combustor was established to investigate the variations of cycle performance and component characteristics under design and off-design conditions. Thereafter, sensitivity analysis of component parameters was conducted to explore the comprehensive reason for change of cycle efficiency increment. The results demonstrated that compared with those of traditional gas turbine, higher cycle performance and lower compressor pressure ratio were gained in rotating detonation gas turbine. Increment of cycle efficiency and cycle net power increment significantly increased with the drop of load, which reached to 0.0248 and 3.261 MW when turbine inlet total temperature was 1450 K and increased to 0.0539 and 4.008 MW when turbine inlet total temperature was 1279 K. Cycle performance was significantly affected by the changes of compressor pressure ratio, compressor efficiency, equivalence ratio of RDC and turbine efficiency, among which turbine efficiency rather than compressor outlet total temperature had the most significant effect on cycle efficiency increment under the calculated conditions. Highlights: A new calculation model of rotating detonation gas turbine cycle is built. Sensitivity analysis of component parameters is carried out. Higher performance and lower compressor pressure ratio are gained in the new cycle. Turbine efficiency has the most significant effect on cycle efficiency increment.